A roadmap for sustainability assessment in the food supply chain. Issue 13 (19th February 2021) - León Bravo, Verónica; Moretto, Antonella; Caniato, Federico
Abstract : Purpose: To develop a roadmap of sustainability practices and assessment mechanisms to advance in the sustainable supply chain (SSC) performance assessment in the food supply chain. The analysis is grounded on the contingency and stakeholder theories. Design/methodology/approach: The study follows a multiple case study approach analyzing the sustainability practices implementation and assessment across different supply chain stages in the food industry in Italy. The set of cases comprises 12 companies in the fresh fruit and vegetables (FFV), and seven companies in the "Balsamic Vinegar of Modena" (BVM) supply chains. Findings: The sustainability practices and assessment in each company in both supply chains according to their objectives are identified. Different stakeholder pressures for sustainability implementation and assessment are analyzed. The contingency factors that foster sustainability assessment are outlined as well. Finally, the study develops a roadmap with five levels of progress considering the groups of practices implemented and the type of assessment applied. Practical implications: The roadmap is a decision-making tool for planning and monitoring progress on SSC performance along five possible levels of progress. While identifying the assessment mechanisms implemented for different kind of sustainability practices, companies can develop a strategy according to their aims and capabilities and stakeholder's expectations. Originality/value: The novelties in this study are threefold. First, the roadmap with five levels of progress. Second, investigating two different food supply chains that allowed for a broader view regarding sustainability practices and assessment. Third, the adoption of stakeholder and contingency theories in SSC studies.